(3ZQGFH GdJfHjgGJ Ydi YLGFH GdJTHjgGJ (B((3aj GdJTHjg Hjf GdCTYGQ(B)s - (3Ydj Hf XGaQ Hf MSjf GdCROj GdNRQLj, CHh GdMSf LeGd GdOjf,J (B613 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd ai JTHjg GdCLQGe GdYdhjI s
(3BNQgG (B:s
(3GdHGH GdSGOS JTHjgGJ eNJdaI s
(3HOhf JGQjNs
(3eQJH Ydi SJI CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B296 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B113s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B502 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1195s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs